A Study on The Effect of Work Environment Stressors on Employees Job Performance - Sarika Patil (AG Volumes, 2021)
In this paper researcher is an attempting to give the realistic view on the association amid work environment stressors and employee job Performance and to decide whether there is an any association between these two variables and what kind of relationship exist. In this paper the researcher review of the current literature will be presented in three distinct parts. The first and second parts include the concepts of work stressors and job performance at work and the last part include the examination of the causal interrelationship between these two variables. Researcher have studied the previous literature and have in-depth interviews with Human Resource, a survey was designed 50 responses were received from the selected industries. The study established that the organizations work environmental factors and other things which influenced the employee jobperformance. The study concluded that the work environment stressors influenced the job performance.